Upaya Diplomasi Indonesia Terhadap Rusia Dalam Rangka Pemulihan Pariwisata Bali Pasca Pandemi COVID-19 - Gunawan, Alexandra Catherine; Dewi, Putu Ratih Kumala (JURNAL DESTINASI PARIWISATA, 2023)
The island of Bali is one of the favorite tourist destinations for international foreigners where the Bali tourism sector is a major contribution to the Indonesian economy. Foreign tourists visiting Bali are quite diverse, but tourists from Russia are always included in the 10th largest ranking of visits to Bali, which is influenced by the good bilateral relations that exist between the two countries. When the Covid-19 pandemic occurred, Bali tourism slumped due to the absence of foreign tourists visiting. Thus, this research was conducted to analyze the efforts made by the Indonesian government to restore Bali tourism by increasing Russian tourist visits to Bali again. This research was conducted using descriptive qualitative research methods using secondary data in the form of literature and statistical data obtained from government agencies using the concepts of commercial diplomacy and bilateral tourism. The results of this study indicate that Indonesia is carrying out commercial diplomacy in the form of tourism promotion involving the private sector, namely the holding of the It's Time for Bali expo in Moscow in March 2022 and the issuance of a Visa on Arrival policy for visits by Russian citizens to Indonesia in April 2022. These efforts have succeeded in drastically increasing visits by Russian tourists to Bali as shown by statistical data from the Bali Provincial Tourism Office. Keywords: Bali tourism, bilateral tourism, commercial diplomacy, covid-19 pandemic